Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
#)Giải :
\(x\left(2x-1\right)\left(x+5\right)-\left(2x^2+1\right)\left(x+4,5\right)=3,5\)
\(\Leftrightarrow\left(2x^2-x\right)\left(x+5\right)-2x^3-9x^2-x-4,5=3,5\)
\(\Leftrightarrow2x^3+10x^2-x^2-5x-2x^3-9x^2-x-4,5=3,5\)
\(\Leftrightarrow-5x-4,5=3,5\)
\(\Leftrightarrow-5x=8\)
\(\Leftrightarrow x=-\frac{8}{5}\)
\(x\left(2x-1\right)\left(x+5\right)-\left(2x^2+1\right)\left(x+4,5\right)=3,5\)
\(\Leftrightarrow\left(2x^2-x\right)\left(x+5\right)-\left(2x^3+9x^2+x+4,5\right)=3,5\)
\(\Leftrightarrow2x^3+10x^2-x^2-5x-2x^3-9x^2-x-4,5=3,5\)
\(\Leftrightarrow-6x=8\)
\(\Leftrightarrow x=\frac{-8}{6}=\frac{-4}{3}\)
\(\Leftrightarrow x\left(2x^2+10x-x-5\right)-\left(2x^3+9x^2+x+4.5\right)=3.5\)
\(\Leftrightarrow2x^3+9x^2-5x-2x^3-9x^2-x-4.5=3.5\)
=>-6x=8
hay x=-4/3
\(x\left(2x-1\right)\left(x+5\right)-\left(2x^2+1\right)\left(x+4.5\right)=3.5\)
\(=>2x^3+10x^2-x^2-5x-2x^3-9x^2-x-4.5-3.5=0\)
\(=>-6x-8=0\)
\(=>-2\left(3x+4\right)=0\)
\(=>3x+4=0\)(vì \(-2\ne0\))
\(=>x=\frac{-4}{3}\)
\(3x^2-3x\left(x-2\right)=36\\ \Rightarrow3x\left(x-x+2\right)=36\\ \Rightarrow6x=36\\ \Rightarrow x=6\)
\(\left(3x^2-x+1\right)\left(x-1\right)+x^2\left(4-3x\right)=\dfrac{5}{2}\\ \Rightarrow3x^3-4x^2+2x-1+\left(4x^2-3x^3\right)=\dfrac{5}{2}\\ \Rightarrow2x-1=\dfrac{5}{2}\\ \Rightarrow x=\dfrac{7}{4}\)
a)
\(\left(x-3\right)\left(x+3\right)-2x=2x\)
\(\Leftrightarrow\left(x-3\right)\left(x+3\right)=2x-2x\)
\(\Leftrightarrow\left(x-3\right)\left(x+3\right)=0\)
\(\Leftrightarrow x-3=0\) hoặc \(x+3=0\)
\(\Leftrightarrow x=3\) \(x=-3\)
Bài 1:
a) Ta có: \(P=1+\dfrac{3}{x^2+5x+6}:\left(\dfrac{8x^2}{4x^3-8x^2}-\dfrac{3x}{3x^2-12}-\dfrac{1}{x+2}\right)\)
\(=1+\dfrac{3}{\left(x+2\right)\left(x+3\right)}:\left(\dfrac{8x^2}{4x^2\left(x-2\right)}-\dfrac{3x}{3\left(x-2\right)\left(x+2\right)}-\dfrac{1}{x+2}\right)\)
\(=1+\dfrac{3}{\left(x+2\right)\left(x+3\right)}:\left(\dfrac{4}{x-2}-\dfrac{x}{\left(x-2\right)\left(x+2\right)}-\dfrac{1}{x+2}\right)\)
\(=1+\dfrac{3}{\left(x+2\right)\left(x+3\right)}:\dfrac{4\left(x+2\right)-x-\left(x-2\right)}{\left(x-2\right)\left(x+2\right)}\)
\(=1+\dfrac{3}{\left(x+2\right)\left(x+3\right)}\cdot\dfrac{\left(x-2\right)\left(x+2\right)}{4x+8-x-x+2}\)
\(=1+3\cdot\dfrac{\left(x-2\right)}{\left(x+3\right)\left(2x+10\right)}\)
\(=1+\dfrac{3\left(x-2\right)}{\left(x+3\right)\left(2x+10\right)}\)
\(=\dfrac{\left(x+3\right)\left(2x+10\right)+3\left(x-2\right)}{\left(x+3\right)\left(2x+10\right)}\)
\(=\dfrac{2x^2+10x+6x+30+3x-6}{\left(x+3\right)\left(2x+10\right)}\)
\(=\dfrac{2x^2+19x-6}{\left(x+3\right)\left(2x+10\right)}\)
\(x\left(2x-1\right)\left(x+5\right)-\left(2x^2+1\right)\left(x+4,5\right)=3,5\)
\(\Rightarrow\left(2x^2-x\right)\left(x+5\right)-2x^3-9x^2-x-4,5=3,5\)
\(\Rightarrow2x^3+10x^2-x^2-5x-2x^3-9x^2-x-4,5=3,5\)
\(\Rightarrow-5x-4,5=3,5\)
\(\Rightarrow-5x=8\)
\(\Rightarrow x=-\dfrac{8}{5}\)